Pengaruh Kepuasan Kerja dalam Meningkatkan Kinerja Pemasaran di Era Digitalisasi - Rutinaias Haholongan; Abidah Ardelia Mulya; Zahwa Khalisha Fuad; Muhammad Fikri Bafagih (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study examines the effect of job satisfaction on employees’ marketing performance in the digital era. Increasing business competition and rapid technological changes require marketing employees to adapt quickly in order to maintain organizational performance. However, many companies still face challenges related to inconsistent marketing performance caused by low employee satisfaction. This research aims to analyze whether job satisfaction significantly influences marketing performance in a digital work environment. A quantitative associative approach was applied in this study. Primary data were collected through questionnaires distributed to 134 marketing employees using a Likert scale. The data were analyzed using simple linear regression with SPSS software. The findings indicate that job satisfaction has a positive and significant effect on marketing performance. The regression coefficient value of 0.675 and significance level of 0.000 confirm that higher job satisfaction contributes to better marketing performance. In addition, the coefficient of determination (R²) of 0.402 shows that job satisfaction explains 40.2% of the variation in marketing performance, while the remaining percentage is influenced by other factors outside the study. These results highlight the importance of improving employee satisfaction to support marketing effectiveness in the digitalization era.